2012
DOI: 10.1016/j.jval.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Health Utility Measured with EQ-5D in Thai Patients Undergoing Peritoneal Dialysis

Abstract: This Thai PD sample yielded higher EQ-5D scores than did other PD populations. To improve the health utility of Thai patients undergoing PD, the significant factors should be addressed. Because our PD sample had a short PD duration, their long-term health utility should be evaluated in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
2
19
4
1
Order By: Relevance
“…The EQ-5D-5L took a very short time about 2 min to complete. Even though EQ-5D-3L was not compared, the ceiling effect of EQ-5D-5L (13.6 %) was lower than those of EQ-5D-3L reported in our previous studies including HIV (28.3 %) [10], diabetes (21.1 %) [33], peritoneal dialysis (18.6 %) [34], and coronary artery disease (33.3 %) [35]. The ceiling effect of EQ-5D-5L of this study was also lower than a limit of 15 % [36] and that of a foreign study conducted in general population with chronic diseases (32.3 %) [20].…”
Section: Discussioncontrasting
confidence: 62%
“…The EQ-5D-5L took a very short time about 2 min to complete. Even though EQ-5D-3L was not compared, the ceiling effect of EQ-5D-5L (13.6 %) was lower than those of EQ-5D-3L reported in our previous studies including HIV (28.3 %) [10], diabetes (21.1 %) [33], peritoneal dialysis (18.6 %) [34], and coronary artery disease (33.3 %) [35]. The ceiling effect of EQ-5D-5L of this study was also lower than a limit of 15 % [36] and that of a foreign study conducted in general population with chronic diseases (32.3 %) [20].…”
Section: Discussioncontrasting
confidence: 62%
“…Another study among Korean patients on haemodialysis reported the HRQOL was 0.704 ± 0.199 (Kang et al, 2015). Sakthong & Kasemsup (2012) reported that the EQ-5D score for patients on peritoneal dialysis in Taiwan was 0.65 ± 0.23, whereas the score for this group in our study was 0.86 ± 0.12. Surprisingly, the mean EQ-5D score for patients in our study was higher than that reported in developed countries (e.g., Japan and South Korea), suggesting that patients in this study were satisfied with their health.…”
Section: Discussioncontrasting
confidence: 80%
“…In one study, the EQ-5D index score was 0.75 ± 0.17 in Japanese HD patients. 18 In peritoneal dialysis patients, Sakthong et al 30 reported that the EQ-5D index score was 0.65 ± 0.23 in Taiwan. We evaluated HRQoL using the EQ-5D in HD patients and the index score was 0.704 ± 0.199.…”
Section: Discussionmentioning
confidence: 99%